Educational Research and Higher Education Reform in Eastern and Central Europa. Red. Erich Leitner. Frankfurt a/M., Berlin, Bern, New York, Paris, Wien 1998, ss. 231, fot. 3, tab. 9 - Hellwig, Jan (Biuletyn Historii Wychowania, 1999)
Educational Research and Higher Education Reform in Eastern and Central Europa. Red. Erich Leitner. Frankfurt a/M., Berlin, Bern, New York, Paris, Wien 1998, ss. 231, fot. 3, tab. 9